2004
DOI: 10.1180/0026461046840208
|View full text |Cite
|
Sign up to set email alerts
|

Skaergaardite, PdCu, a new platinum-group intermetallic mineral from the Skaergaard intrusion, Greenland

Abstract: Skaergaardite, PdCu, is a new mineral discovered in the Skaergaard intrusion, Kangerdlugssuaq area, East Greenland. It occurs in a tholeitiic gabbro associated with plagioclase, clinopyroxene, orthopyroxene, ilmenite, titanian magnetite, fayalite and accessory chlorite-group minerals, ferrosaponite, a member of the annite-phlogopite series, hornblende, actinolite, epidote, calcite, ankerite, apatite and baddeleyite. The mineral is found in composite microglobules composed of bornite, chalcocite, digenite, chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 10 publications
(14 reference statements)
1
34
0
3
Order By: Relevance
“…In the JM-Reef of the Stillwater Complex, detailed mineralogical analysis (Godel and Barnes 2008a;Godel and Barnes 2008b) of altered samples revealed the presence of Pd-Cu alloys (with composition similar to Skaergaardite (Rudashevsky et al 2004)) and to a lesser extent Pd sulfides observed either as interstitial phase between magnetite crystal or as small veinlets crosscutting the base-metal sulfide minerals ( Fig. 9.22).…”
Section: Hydrothermal Remobilization Of the Platinum-group Elementsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the JM-Reef of the Stillwater Complex, detailed mineralogical analysis (Godel and Barnes 2008a;Godel and Barnes 2008b) of altered samples revealed the presence of Pd-Cu alloys (with composition similar to Skaergaardite (Rudashevsky et al 2004)) and to a lesser extent Pd sulfides observed either as interstitial phase between magnetite crystal or as small veinlets crosscutting the base-metal sulfide minerals ( Fig. 9.22).…”
Section: Hydrothermal Remobilization Of the Platinum-group Elementsmentioning
confidence: 97%
“…f AP and PV Reefs of the Penikat intrusion. The data are extracted from and McDonald 2007; Locmelis et al 2010;Oberthür et al 2003;Osbahr 2012;Osbahr et al 2013;Rudashevsky et al 2009;Rudashevsky et al 2004;van der Merwe et al 2012;Yudovskaya et al 2012). These studies complemented the extensive literature available (e.g.…”
Section: Platinum-group Mineralsmentioning
confidence: 99%
“…Detailed descriptions of the mineralogy of the Platinova Reef can be found in Bird et al (1991), Andersen et al (1998), Rudashevsky et al (2004), Cabri et al (2005), Nielsen et al (2005), Godel et al (2014), Rudashevsky et al (2014;2015) and Nielsen et al (2015). The latter compiles and summarizes a series of Geological Survey of Greenland and Denmark reports that record details of more than 4000 PGM (e.g., Nielsen et al 2003;Rudashevsky et al 2009).…”
Section: Sulfide Abundances Mineralogy and Textures In The Platinovamentioning
confidence: 99%
“…2c, f, j) and PGM. Previous studies by Bird et al (1991), Andersen et al (1998) Rudashevsky et al (2004), Cabri et al (2005), Nielsen et al (2005;2015 and references therein) and McDonald et al (2009) have shown that for the main part of the Platinova Reef, the dominant PGM are the Pd-Cu alloys skaergaardite (PdCu) and nielsenite (PdCu 3 ) along with tetra-auricupride (AuCu) in the Au zone. The Au content of the Pd-Au-Cu alloys increases with height in line with the upward bulk rock Pd/Au ratio decrease (Fig.…”
Section: Mineralogy Of Sulfide Blebsmentioning
confidence: 99%
See 1 more Smart Citation